Application of yeasts fortified with microelements – Review - Molnár, Judit; Ásványi, Balázs (Acta Agraria Debreceniensis, 2017)
Microelements are increasingly becoming into the focus of interest from both a point of view of nutrition science and feeding. An always growing care must be paid to the microelements coverage both in human and animal organisms because of incorrect alimentation habits andunsatisfactory feedstuff nutrition value. For the increased supply of the micro-nutrients, enrichment or fortification with microelements can not only be realized with traditional foodstuffs and forage but there are already alternative ways such as single-cell proteins from yeasts directly enriched or fortified with microelements for the purpose.We would like to draw the attention that the production of these items is more favourable in comparison with traditional foodstuffs or forage since yeasts are capable to multiply microelement levels compared to their original state, and establish organic bonds with them.For this purpose, we explored and analysed the scientific literature, studies and research results on this subject, that is why we stressed the significance of yeasts, the features and health effects of certain microelements, as well as the possibilities for use of yeasts enriched with micro-nutrients.